Role of spatial and temporal vegetation heterogeneity from fire-grazing interactions to the assembly of tallgrass prairie spider communities - Gómez, Jesús Enrique (Kansas State University, 2017)
North American tallgrass prairie is a dynamic ecosystem that evolved with variable regimes of fire and grazing interactions (pyric herbivory), and variable mid-continental weather. Combined, these ecological factors create a shifting mosaic of plant communities that create heterogeneous and structurally complex habitats that move around across the landscape in time and space. The overarching goal of my dissertation was to study how bottom-up habitat templates created in response to fire-grazing interactions influence the community structure of spiders, key arthropod predators in grassland food-webs. Spiders are a ubiquitous and diverse group of terrestrial predators that partition their habitat at fine scales with species distributions and abundances that are sensitive to habitat structure. Primary hypotheses examined include: (H1) Spider density, species diversity, species evenness and functional richness of hunting strategies should increase as the spatial heterogeneity of habitat structure and overall habitat productivity increases, as predicted by the habitat complexity and heterogeneity hypothesis. (H2) Pyric herbivory indirectly determines spider community structure through is effect on vegetation structure and spatial heterogeneity, thereby promoting the formation of a mosaic of spider species assemblages that track changes in the distribution of key habitat resources. My research takes advantage of a long-term, watershed-level manipulations of fire frequency and bison grazing across a topographically variable landscape at Kansas State University’s Konza Prairie Biological Station, a tallgrass prairie research site near Manhattan KS. Spider communities were sampled for three years at 23 sites representative of multiple habitat types ranging from low-stature grass-dominated sites to grassland-gallery forest transition zones. In addition, a field experiment was performed to test the hypothesis that vegetation structure contributes directly to web-builder abundance and web-type richness of spiders in open grasslands. Here, the availability of structure for web placement was increased by adding dead woody stems along transects in three watersheds that differed in burn histories and existing habitat structure in the absence of grazing. Results were consistent with the three key hypotheses. Species diversity and the functional diversity of spiders increased as the spatial heterogeneity and overall structure of habitat increased in response to fire-grazing interactions. Vegetation heterogeneity influenced spider community responses most strongly in the summer. Structural complexity of vegetation influenced spider diversity, species evenness and richness of hunting strategies throughout the growing season, becoming most important by the end of the growing season. The transitional ecotone between grasslands and woodlands supported a hotspot for spider density, species diversity and richness of hunting strategies along vegetation gradients (H1), and among habitat types (H2). Increasing the availability of web-anchoring structures in open grasslands led to increased web-builder density in open grassland, particularly for small and medium sized orb-web species that took advantage of increased physical structure. Disturbance from pyric herbivory indirectly promoted dynamic and malleable assemblages of spider species that coexisted in syntopy through effects on vegetation structure and its availability in time and space. Changes in habitat structure and heterogeneity as spatially and temporally shifting mosaics of habitat type increased the overall spider diversity at the landscape scale.
Keywords: Spider community; Habitat structure; Konza Prairie Biological Station; Spatial and temporal heterogeneity; Fire and grazing interactions